Diversity And Infestation Intensity Of Bactrocera Spp. In Local Red Chili (Capsicum annuum L.) Varieties In West Sumatra - Nguyễn, Phước Sang; Norvi Nelly; Reflinaldon; Hidrayani (International Seminar on Plant Protection, 2025)
Red chili (Capsicum annuum L.) is an essential horticultural product in West Sumatra both commercially and culturally,. Sadly, its output has experienced a substantial decline recently, primarily as a result of increased biotic pressures, particularly from tephritid fruit flies (Bactrocera spp.). This study aimed to clarify the diversity and infestation intensity of Bactrocera species, as well as their correlation with regional chili types and four important chili-producing regencies. Using morphological taxonomic keys, species were identified during the October 2024 to March 2025 period by extensive field surveys and Lynfield trapping techniques. Three species of Bactrocera were identified: B. umbrosa (0.3%), B. carambolae (0.8%), and B. dorsalis (98.9% of all catches). Across all sites, the species composition showed substantial pest dominance, especially of B. dorsalis, but low overall biodiversity. Agam had the most diversity, although Simpson, Evenness, and Shannon diversity indices differed by location. Strong positive correlations between B. dorsalis density and infestation rates of both plants (r = 0.70) and fruit (r = 0.68). Likewise, there were notable positive relationships between altitude and infection intensity (plant r = 0.88; fruit r = 0.73), indicating that mid- to high-altitude study zones had higher levels of pest activity. Kuhay showed significant resilience, but Rawit and Keriting were the most susceptible of the four chili types. These results emphasize the necessity of incorporating agroecological context and varietal resistance into targeted integrated pest management (IPM) methods for upland chili systems, as well as the dominance of B. dorsalis as a pest concern.